(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The article analyzes the construction and constant re-elaboration of the canonical status of the play Wedding Dress through observation of the paths, speeches and receptions of some of its productions. Aiming to understand this process of legitimizing a specific meaning and reading over the decades, the meanings of the seasons of Os Comediantes and some representative performances are analyzed, namely, the 1955 one by Teatro Suicida, the 1958 and 1965 one, directed by Sérgio Cardoso, and the 1976 reconstruction carried out by Ziembinski himself.